Avian influenza viruses in humans: lessons from past outbreaks. Issue 1 (14th December 2019) - Li, Yao-Tsun; Linster, Martin; Mendenhall, Ian H; Su, Yvonne C F; Smith, Gavin J D
Abstract: Background: Human infections with avian influenza viruses (AIV) represent a persistent public health threat. The principal risk factor governing human infection with AIV is from direct contact with infected poultry and is primarily observed in Asia and Egypt where live-bird markets are common. Areas of agreement: Changing patterns of virus transmission and a lack of obvious disease manifestations in avian species hampers early detection and efficient control of potentially zoonotic AIV. Areas of controversy: Despite extensive studies on biological and environmental risk factors, the exact conditions required for cross-species transmission from avian species to humans remain largely unknown. Growing points: The development of a universal ('across-subtype') influenza vaccine and effective antiviral therapeutics are a priority. Areas timely for developing research: Sustained virus surveillance and collection of ecological and physiological parameters from birds in different environments is required to better understand influenza virus ecology and identify risk factors for human infection.